Artificial vision algorithm for earth station location from CubeSats in narrow beam optical communications. Issue 1 (1st September 2022) - Medina, I; Santiago, L; Hernández Gómez, J J; Castillo, R; Couder Castañeda, C
Abstract: The use of CubeSats promises several advantages within a low economical budget margin for different missions. Nowadays, data transfer through optical channels (lasercom) is considered a potential technology for satellite wireless communications, providing several advantages in terms of data transfer rate with lower energy consumption. However, a main drawback is the location of the Optical Ground Station (OGS). Therefore, an artificial vision algorithm for the processing of images captured by the camera of a CubeSat is proposed in this work, in order to carry out the identification and recognition of an OGS by means of a beacon signal, to aid the Pointing, Acquisition and Tracking (PAT) onboard subsystem for the communication's stage.